University-based physical education as a structured temporal and spatial opportunity for shaping health-oriented lifestyles - Lu Zhang; Tao Zhong; Kui Dong (Frontiers in Public Health)
BackgroundRegular physical activity is widely recognized for its health benefits, including improved cardiovascular function and reduced risk of chronic diseases. However, insufficient physical activity remains prevalent among university students, many of whom fail to meet recommended guidelines. University-based physical education (PE) programs play a critical role in fostering active lifestyles and promoting health-oriented behaviors among young adults. This study aimed to examine the association between participation in PE classes and the adoption of health-oriented behaviors among Chinese college students, particularly in the 3rd and 4th years, when participation in PE is voluntary.MethodsA cross-sectional study was conducted with 1,902 3rd- and 4th-year university students (mean age: 20.94 years; 59.2% female). The survey collected data on demographic (age and gender), socioeconomic status, body mass index (BMI), and some health-related behaviors such as dietary habits, smoking status, physical activity levels, and frequency of PE class attendance.ResultsResults showed 44.23% of students were physically inactive, 8.1% were smokers, and 61.18% had an unhealthy diet. Male students had higher rates of smoking, obesity, and unhealthy diets compared to females. Participation in PE classes was associated with lower risks of obesity, unhealthy diets, and physical inactivity. Logistic regression analyses confirmed that PE attendance was a protective factor against these unhealthy behaviors, with significant gender-based differences observed in lifestyle patterns.ConclusionThis study highlights the importance of PE in promoting healthier lifestyles among university students and underscores the need for continued access to structured PE programs throughout the undergraduate years.